Comparative study of consumers’ knowledge and attitudes towards food safety and purchase intention of night market foods containing poultry in low and high food poisoning cases states - Lieong, Sook Theng; Siti Aisyah Mohammed Adnan,; Normardiana Mohammad Jaafar,; Siti Nur’afifah Jaafar,; Norainy Mahyudin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study was conducted to compare the level of consumers’ knowledge and attitude towards food safety as well as consumers’ intention to purchase night market food precisely food containing poultry based on food hygiene practice of food handlers in two different states i.e. Selangor and Kuala Lumpur. Selangor represents a state with high food poisoning cases while Kuala Lumpur has low food poisoning cases. Two hundred night market consumers for each sampling location were approached. Data was statistically analyzed using SPSS program version 20.0. Generally, respondents’ knowledge of food safety score was significantly different for consumers in Kuala Lumpur (M=14.37, SD=3.75) and Selangor (M=15.10, SD=3.36), (t=2.107, df=429) at p<0.05. Analysis also showed that there were significant differences in the attitude score among consumers in Kuala Lumpur (M=4.71, SD=0.39) and Selangor (M=4.48, SD=0.28), (t=7.085, df=414) at p<0.05. Results revealed that consumers’ intention to purchase night market food in Selangor and Kuala Lumpur are statistically different depending on food handlers’ practices (e.g. tasting food using fingers and hand palm, wear nail polish, touch cooked food with bare hands and etc.) This empirical study served status of consumers’ knowledge, attitude and intention to purchase regarding food safety which could be applied to implement repeated food safety education programs to improve quality of life in local communities.